Workers' perceptions of climate change related extreme heat exposure in South Australia: a cross-sectional survey - Jianjun Xiang; Alana Hansen; Dino Pisaniello; Peng Bi (BMC, 2016)
Abstract Background Occupational exposure to extreme heat without sufficient protection may not only increase the risk of heat-related illnesses and injuries but also compromise economic productivity. With predictions of more frequent and intense bouts of hot weather, workplace heat exposure is presenting a growing challenge to workers' health and safety. This study aims to investigate workers' perceptions and behavioural responses towards extreme heat exposure in a warming climate. Methods A cross-sectional questionnaire survey was conducted in 2012 in South Australia among selected outdoor industries. Workers' heat risk perceptions were measured in the following five aspects: concerns about heat exposure, attitudes towards more training, policy and guideline support, the adjustment of work habits, and degree of satisfaction of current preventive measures. Bivariate and multivariate logistic regression analyses were used to identify factors significantly associated with workers' heat perceptions. Results A total of 749 respondents participated in this survey, with a response rate of 50.9 %. A little more than half (51.2 %) of respondents were moderately or very much concerned about workplace heat exposure. Factors associated with workers' heat concerns included age, undertaking very physically demanding work, and the use of personal protective equipment, heat illness history, and injury experience during hot weather. Less than half (43.4 %) of the respondents had received heat-related training. Workers aged 25-54 years and those with previous heat-related illness/injury history showed more supportive attitudes towards heat-related training. The provision of cool drinking water was the most common heat prevention measure. A little more than half (51.4 %) of respondents were satisfied with the current heat prevention measures. About two-thirds (63.8 %) of respondents agreed that there should be more heat-related regulations and guidelines for working during very hot weather. More than two-thirds (68.8 %) of the respondents were willing to adjust their current work habits to adapt to the likely increasing extreme heat, especially those with previous heat illness experience. Conclusions The findings suggest a need to strengthen workers' heat risk awareness and refine current heat prevention strategies in a warming climate. Further heat educational programmes and training should focus on those undertaking physically demanding work outdoors, in particular young workers and those over 55 years with low education levels.